Quantification of AMPA receptor subunits and RNA editing-related proteins in the J20 mouse model of Alzheimer’s disease by capillary western blotting - Milham, Luke T.; Morris, Gary P.; Konen, Lyndsey M.; Rentsch, Peggy; Avgan, Nesli; Vissel, Bryce (Frontiers in Molecular Neuroscience, 2024)
Introduction Accurate modelling of molecular changes in Alzheimer’s disease (AD) dementia is crucial for understanding the mechanisms driving neuronal pathology and for developing treatments. Synaptic dysfunction has long been implicated as a mechanism underpinning memory dysfunction in AD and may result in part from changes in adenosine deaminase acting on RNA (ADAR) mediated RNA editing of the GluA2 subunit of AMPA receptors and changes in AMPA receptor function at the post synaptic cleft. However, few studies have investigated changes in proteins which influence RNA editing and notably, AD studies that focus on studying changes in protein expression, rather than changes in mRNA, often use traditional western blotting. Methods Here, we demonstrate the value of automated capillary western blotting to investigate the protein expression of AMPA receptor subunits (GluA1-4), the ADAR RNA editing proteins (ADAR1-3), and proteins known to regulate RNA editing (PIN1, WWP2, FXR1P, and CREB1), in the J20 AD mouse model. We describe extensive optimisation and validation of the automated capillary western blotting method, demonstrating the use of total protein to normalise protein load, in addition to characterising the optimal protein/antibody concentrations to ensure accurate protein quantification. Following this, we assessed changes in proteins of interest in the hippocampus of 44-week-old J20 AD mice. Results We observed an increase in the expression of ADAR1 p110 and GluA3 and a decrease in ADAR2 in the hippocampus of 44-week-old J20 mice. These changes signify a shift in the balance of proteins that play a critical role at the synapse. Regression analysis revealed unique J20-specific correlations between changes in AMPA receptor subunits, ADAR enzymes, and proteins that regulate ADAR stability in J20 mice, highlighting potential mechanisms mediating RNA-editing changes found in AD. Discussion Our findings in J20 mice generally reflect changes seen in the human AD brain. This study underlines the importance of novel techniques, like automated capillary western blotting, to assess protein expression in AD. It also provides further evidence to support the hypothesis that a dysregulation in RNA editing-related proteins may play a role in the initiation and/or progression of AD.